Contending institutional logics, illegitimacy risk and management accounting: A case study analysis of study programme calculations in a Polish public university. Issue 4 (30th January 2020) - Łada, Monika; Kozarkiewicz, Alina; Haslam, Jim
Abstract : Purpose: This article explores the influence of duality in institutional logics on internal accounting, with a focus on a Polish public university. More particularly, we answer the research question: how does illegitimacy risk arising from the divergent pressures of the institutional environment impact management accountings in this institution? Design/methodology/approach: This paper seeks to uncover intricacies of notions of internal legitimacy façade, decoupling and counter-coupling in practice. It explores details of organizational responses involving management accounting aimed at reducing illegitimacy risk. Achieving good organizational access, the authors adopt a qualitative case study approach involving contextual appreciation/document analysis/participant observation/discussion with key actors: facilitating building upon theoretical argumentation through finding things out from the field. Findings: The authors uncover and discuss organizational solutions and legitimizing manoeuvres applied, identifying four adaptation tactics in the struggle to support legitimacy that they term 'ceremonial calculations', 'legitimacy labelling', 'blackboxing' and 'shadow management accounting'. These can be seen in relation to decoupling and counter-coupling. Ceremonial calculations supported the internal façade. Shadow management accounting supported pro-effectiveness. Legitimacy labelling and blackboxing helped bind these two organizational layers, further supporting legitimacy. In interaction the four tactics engendered what can be seen as a 'counter-coupling' of management accounting. The authors clarify impacts for management accounting. Research limits/implications: The usual limitations of case research apply for generalizability. Theorizing of management accounting in relation to contradictory logics is advanced. Practical implications: The article illuminates how management accounting can be understood vis-à-vis contradictory logics. Originality value: Elaboration of the tactics and their interaction is a theoretical and empirical contribution. Focus on a Polish university constitutes an empirical contribution.